The effect of synthesis condition on the growth of ZnO nanostructure via hydrothermal method - Ramli, Nurul Hidayah (2019)
Zinc oxide (ZnO) nanostructure was synthesized via hydrothermal method by varied the pH value of precursor. The effect of different pH precursor on morphological structure, optical and physical properties of ZnO nanostructures was investigated. The sample was characterized with X-ray diffraction (XRD), Scanning electron microscope (SEM) and Ultraviolet-Visible (UV-Vis) spectroscopy. X-ray diffraction method (XRD) revealed the ZnO nanostructure exhibit the hexagonal wurtzite structure and the average crystallite size of ZnO nanoparticle is calculated. Scanning electron microscope (SEM) shows the variety of surface morphology of ZnO nanostructure by varying pH of the precursor. Hexagonal nanorod is obtained at pH 7, pH 8 and pH 9 whereas hexagonal nanoflower is obtain at pH 10 and pH 11. UV-Vis spectroscopy shows the absorption or reflectance of zinc oxide was same with theoretical value of ZnO and optical band gap determination shows the direct band gap of the ZnO synthesized with different pH value is lower than actual band gap value of ZnO. The characterization of the ZnO nanostructures via hydrothermal method and the morphology of the sample shows the nanostructures like nanorod and nanoflower was successfully obtained.